Audio-tactile guide in polyester resin: a proposal for a didatic material model aiming at blind education - Tanhoffer, Claudia Maria Sallai (2020)
This article is the description of the development of a methodology, which is similar to a tutorial, for reproducing materials that can be used as a teaching resource in disciplines whose focus is macroscopic morphology, such as Paleontology or Animal or Plant Anatomy and Geology. The process uses silicone rubber and polyester resin to reproduce parts, and an interface, via QR-Code, that takes the user to a narration of the contents posted on the YouTube digital platform. Its objectives were to create an approach that allows duplicating pieces of didactic value, which normally could not be made available for manipulation by students, with a greater focus on education for the blind, in which "touching means seeing" and that manipulation is essential, the methodology allows us to add marks on the texture of the piece, such as the Braille Alphabet. To make the material definitely inclusive, we propose to link the object of interest to a digital platform, and in this case, YouTube via QR-code, where post an audio narrative. Thus, it is possible to use in home studies or in classroom teaching methodologies in which the student is the protagonist. As a result, we obtained a quality copy of a material, usually very expensive or for other inaccessible reasons, whose inputs are low-cost and easily acquired, in addition to being able to be made in the facilities of a school laboratory.